The Democracy Project : a history, a crisis, a movement - Graeber, David (Spiegel & Grau, 2013)
A bold rethinking of the most powerful political idea in the world--democracy--and the story of how radical democracy can yet transform America. Democracy has been the American religion since before the Revolution--from New England town halls to the multicultural democracy of Atlantic pirate ships. But can our current political system, one that seems responsive only to the wealthiest among us and leaves most Americans feeling disengaged, voiceless, and disenfranchised, really be called democratic? And if the tools of our democracy are not working to solve the rising crises we face, how can we--average citizens--make change happen? David Graeber, one of the most influential scholars and activists of his generation, takes readers on a journey through the idea of democracy, provocatively reorienting our understanding of pivotal historical moments, and extracts their lessons for today.--From publisher description.